1969
DOI: 10.1083/jcb.43.3.396
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF THE MODE OF NUTRITION ON THE DIGESTIVE SYSTEM OF OCHROMONAS MALHAMENSIS

Abstract: The intracellular distribution and level of acid hydrolases in Ochromonas malhamensis were studied in cells grown osmotrophically in a defined medium, in a carbon-free starvation medium, and during phagotrophy in each of these media . By cytochemical techniques, little enzymic reaction product was observed in the vacuoles of osmotrophic cells grown in the defined medium . Starved cells, however, contained autophagic vacuoles and cannibalized other Ochromonas cells . Dense enzymic reaction product was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The planktonic flagellate Ochromonas, the subject of the experiments reported here, can take up dissolved organic carbon (DOC) compounds osmotrophically (Stoltze et al, 1969;Holen & Boraas, 1995), is an important consumer of bacteria (Daley, Morris & Brown, 1973;Zubkov et al, 2001;Schmidtke et al, 2006) and can also prey on small eukaryotic phytoplankton (Boraas, Seale & Boxhorn, 1998). Thus, Ochromonas is a consummate generalist, with an ability to garner resources and energy via a striking variety of trophic pathways, but it is an inferior competitor against autotrophic and heterotrophic specialists.…”
Section: Introductionmentioning
confidence: 99%
“…The planktonic flagellate Ochromonas, the subject of the experiments reported here, can take up dissolved organic carbon (DOC) compounds osmotrophically (Stoltze et al, 1969;Holen & Boraas, 1995), is an important consumer of bacteria (Daley, Morris & Brown, 1973;Zubkov et al, 2001;Schmidtke et al, 2006) and can also prey on small eukaryotic phytoplankton (Boraas, Seale & Boxhorn, 1998). Thus, Ochromonas is a consummate generalist, with an ability to garner resources and energy via a striking variety of trophic pathways, but it is an inferior competitor against autotrophic and heterotrophic specialists.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, clearance rates on other viruses might provide estimates much higher (up to 100 %) than those reported. Furthermore, several authors (Muller et al 1965, Stolze et al 1969, Wetzel & Korn 1969, Dubowsky 1974 have shown that the digestive system in a variety of protozoa is activated upon the formation of particle-containing vacuoles. The results we obtained using viruses that were labelled with an FITC-conjugated antibody also suggest that digestion of food particles is rapidly initiated.…”
Section: Ingestion and Digestion Rates Of Virusesmentioning
confidence: 99%
“…Barlow and Triemer (1986) observed acid phosphatase activity in the Golgi cisternae and ER of the heterotrophic dinoflagellate, C. cohnii. Acid phosphatase activity has also been detected in lysosome-like structures, the ER, and the Golgi complex of many non-dinoflagellate protists (Sommer and Blum, 1965;Elliott and Clemmons, 1966;Dembitzer, 1968;Stoltze et al, 1969;McAlpine, 1970;Brooker, 1971;Gomez et al, 1974;Langreth and Balber, 1975;Ryter and Bowers, 1976;Grab et al, 1997). Smaller ELF-97 deposits occurred throughout the cytoplasm in some P. shumwayae cells.…”
Section: Discussionmentioning
confidence: 94%